Advanced Homomorphic Encryption for Cloud Data Security - D. Chandravathi; P.V. Lakshmi (Society of Visual Informatics, 2017)
This paper aims to provide security of data in the Cloud using Multiplicative Homomorphic Approach. Encryption process is done with RSA algorithm. In this RSA algorithm, Shor’s algorithm is used for generating Public key Component, which enhances the security. Shor’s algorithm plays as important role in generating public key. Plain Text Message is encrypted with Public Key to generate Cipher Text and for decryption Chinese Remainder Theorem (CRT) is used to speed up the computations. By doing so, it shows how the CRT representation of numbers in Zn can be used to perform modular exponentiation about much more efficiently using three extra values pre-computed from the prime factors of n. Hence, security is enhanced in the cloud provider.